TRANSFORMING LINGUO-COGNITIVE SKILLS IN LEARNERS THROUGH THE PROBLEM-BASED LEARNING (PBL) METHOD - Rakhimov Mansur Odiljonovich (Bright Mind Publishing, 2025)
The need for graduates who have exceptional cognitive and linguistic abilities in addition to extensive subject understanding is at the forefront of 21st-century education. This essay examines how the Problem-Based Learning (PBL) methodology has the potential to revolutionize the way students acquire integrated linguo-cognitive abilities. PBL, which breaks from conventional, didactic teaching paradigms, engages learners in real-world, complicated issues that need them to use inquiry, cooperation, and problem-solving skills. This paper outlines the ways in which PBL encourages this symbiosis through a synthesis of current educational literature and theoretical frameworks, demonstrating that the process naturally and simultaneously cultivates higher-order cognitive skills, such as critical thinking, problem-solving, and metacognition, as well as advanced linguistic competencies, such as disciplinary discourse, academic vocabulary, and persuasive communication. It investigates how the PBL cycle—from problem analysis to reflection—supports the acquisition of both conceptual knowledge and the language necessary to express it. The essay concludes that PBL is more than just a teaching method; it's a potent environment for turning passive learners into adaptable, expressive, and independent thinkers who are ready for the cognitive and communicative challenges of today's civic and professional world.
Keywords: Problem-based learning, linguo-cognitive skills, critical thinking, academic language, collaborative learning, metacognition, disciplinary discourse, student-centered learning.